2018
DOI: 10.12669/pjms.345.15300
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and characteristics of Traumatic Tympanic Membrane perforation

Abstract: Objective:To determine incidence and characteristics of traumatic Tympanic Membrane perforation in a tertiary care hospital.Methods:This descriptive cross sectional study was conducted at the Department of ENT, MTI/LRH, Peshawar from August to December 2017. After well informed consent a detailed history was taken; thorough examination of ENT was carried out. Pure Tone Audiometry (PTA) of all included patients was performed by same senior audiometrician. The data were collected on predesigned proforma and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…These findings were consistent with the findings of another study done by Rabbani SMG et al who reported that slapping for is responsible for the majority of cases of perforation of tympanic membrane 1 . Another study done by Fazal I. Wahid and Sajid Rashid Nagra also reported slap as cause of perforation of tympanic membrane in majority of their cases 8 . In contrary to our results, another study from Iraq reported that blast was the main cause of perforation of tympanic membrane 2 .…”
Section: Discussionmentioning
confidence: 90%
“…These findings were consistent with the findings of another study done by Rabbani SMG et al who reported that slapping for is responsible for the majority of cases of perforation of tympanic membrane 1 . Another study done by Fazal I. Wahid and Sajid Rashid Nagra also reported slap as cause of perforation of tympanic membrane in majority of their cases 8 . In contrary to our results, another study from Iraq reported that blast was the main cause of perforation of tympanic membrane 2 .…”
Section: Discussionmentioning
confidence: 90%
“…In Gray’s Anatomy, 1 the classical textbook, the height and width of the membrane have been given as 9-10 mm and 8-9 mm, respectively. However, 21 , 22 these measurements were reported by some otorhinolaryngologists as 10 mm and 5 mm, respectively. The possible reasons for differences in the diameters of the tympanic membrane or the TR were listed as follows: methodology (e.g., in situ or ex situ measurements), demographic data (e.g., region), and c) technique (e.g., dissection or ultrasonographic imaging).…”
Section: Discussionmentioning
confidence: 93%
“…It protects the middle ear cleft and amplifies and transmits sound waves from external auditory canal through ossicular chain to oval window and cochlea due to its vibratory characteristic. 3 TM could be ruptured by trauma due to hair pin, matchstick or unskilled attempts to remove a foreign body, sudden change in air pressure e.g., a slap on the ear or a sudden blast, pressure by a fluid column, e.g., diving or forceful syringing, fracture of temporal bone etc. 1 The common manifestations of traumatic TM perforation are sudden severe pain, bleeding, hearing impairment, tinnitus and dizziness.…”
Section: Introductionmentioning
confidence: 99%
“…1 The common manifestations of traumatic TM perforation are sudden severe pain, bleeding, hearing impairment, tinnitus and dizziness. 3 This symptomatology depends upon the site and severity of perforation. Treatment of TTMP range from inactive watchful waiting, active intervention to surgical intervention.…”
Section: Introductionmentioning
confidence: 99%